The Performance of Snack MSMES in the Covid-19 Pandemic (A Review from the Income Side) - Helmi Azahari; Endah Fantini; Samsudin Samsudin; Noviandari Sari Utami; Ade Suryana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to find out how the performance of micro, small and medium enterprises (MSMEs) snacks during the Covid-19 pandemic. Does the Covid-19 pandemic affect the continuity of the MSME Snack business? To see the performance of MSMEs is measured based on the Balance Score Card, however in this study, research is limited to only looking at the financial side (income). This study uses a qualitative method with two informants, namely dodol and snack MSMEs in Garut, West Java and kemplang (baked crackers) MSMEs in Palembang, South Sumatra. As a result, it turns out that the Covid-19 pandemic has not affected snack MSMEs. Turnover (gross income) of MSMEs snacks actually increased during the Covid-19 pandemic. Anticipating the limited human travel during the Covid-19 pandemic, MSME entrepreneurs also sell through online stores and market places. However, the sales turnover is not as big as direct sales in stores. There are still more buyers who come to buy snacks at the shop.